2014
DOI: 10.2337/db13-1005
|View full text |Cite
|
Sign up to set email alerts
|

OATP1B3 Is Expressed in Pancreatic β-Islet Cells and Enhances the Insulinotropic Effect of the Sulfonylurea Derivative Glibenclamide

Abstract: Organic anion transporting polypeptide OATP1B3 is a membrane-bound drug transporter that facilitates cellular entry of a variety of substrates. Most of the previous studies focused on its hepatic expression and function in hepatic drug elimination. In this study, we report expression of OATP1B3 in human pancreatic tissue, with the abundance of the transporter localized in the islets of Langerhans. Transport studies using OATP1B3-overexpressing MDCKII cells revealed significant inhibition of the cellular uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Organic anion transporting polypeptides OATP1B1-3 are drug transporters relevant for cellular drug entry and thus mechanism of action of most drugs [Picard et al 2010]. Recently expression of OATP1B3 was found to be in the islets of Langerhans of human pancreas, and facilitating cellular entry of glibenclamide [Meyer Zu Schwabedissen et al 2014]. Thus, OATP1B3 likely are affected by drug-drug interactions or by genetic variants, influencing efficacy of SU or Meteglinids.…”
Section: Susmentioning
confidence: 99%
“…Organic anion transporting polypeptides OATP1B1-3 are drug transporters relevant for cellular drug entry and thus mechanism of action of most drugs [Picard et al 2010]. Recently expression of OATP1B3 was found to be in the islets of Langerhans of human pancreas, and facilitating cellular entry of glibenclamide [Meyer Zu Schwabedissen et al 2014]. Thus, OATP1B3 likely are affected by drug-drug interactions or by genetic variants, influencing efficacy of SU or Meteglinids.…”
Section: Susmentioning
confidence: 99%
“…This protein has the ability to transport small anion molecules including certain drugs or contrast media across the cell membrane. OATP1B3 are expressed by the cells in the liver, small intestine, and even islet cells, and in particular OATP1B3 in the islet cells can enhance the insulinotropic effect of the sulfonylurea derivative glibenclamide . Gadolinium‐ethoxybenzyl‐diethylenetriaminepentaacetic acid (Gd‐EOB‐DTPA), a clinically approved MRI contrast agent widely applied in clinical liver imaging can be transported across cell membranes mediated mainly by the OATP family, especially OATP1B1 and OATP1B3 (OATP8).…”
Section: Introductionmentioning
confidence: 99%
“…Although the expressions of the OATP1B1 and OATP1B3 transporters are assumed to be liver-specific, recent evidence (Meyer zu Schwabedissen et al 2014) indicated the presence of the OATP1B3 transporter in pancreatic β cells. A detailed gene expression and immunohistochemical study by Kim et al (2017) now shows high expression of OATP1B3, OATP2B1 and OATP1Al mRNA in human pancreatic islets, and a high association of OATP1B3 immunostaining with glucagon-producing pancreatic α cells.…”
Section: Oatp1b3 and Oatp2b1 Transporter Expression In Human Pancreatmentioning
confidence: 99%